Biophysical quantification of reorganization dynamics of human pancreatic islets during co-culture with adipose-derived stem cells. Issue 12 (18th May 2022) - Torres-Castro, Karina; Azimi, Mohammad S.; Varhue, Walter B.; Honrado, Carlos; Peirce, Shayn M.; Swami, Nathan S.
Abstract : Reorganization dynamics of human islets during co-culture with adipose stem cells depends on islet size and the heterogeneity can be assessed based on biomechanical opacity of individual islets. Abstract : Islet transplantation is a potential therapy for type 1 diabetes, but it is expensive due to limited pancreas donor numbers and the variability in islet quality. The latter is often addressed by co-culture of harvested islets with stem cells to promote in vitro remodeling of their basement membrane and enable expression of angiogenic factors for enhancing vascularization. However, given the heterogeneity in islet size, shape and function, there is a need for metrics to assess the reorganization dynamics of single islets over the co-culture period. Based on shape-evolution of individual multi-cell aggregates formed during co-culture of human islets with adipose derived stem cells and the pressures required for their bypass through microfluidic constrictions, we present size-normalized biomechanical metrics for monitoring the reorganization. Aggregates below a threshold size exhibit faster reorganization, as evident from rise in their biomechanical opacity and tightening of their size distribution, but this size threshold increases over culture time to include a greater proportion of the aggregates. Such biomechanical metrics can quantify the subpopulation of reorganized aggregates by distinguishing them versus those with incomplete reorganization, over various timepoints during the co-culture.